Sulfation and human cytosolic sulfotransferases - Falany, Charles (Henry Stewart Talks, 2007)
Cytosolic sulfotransferase (SULTs) gene family, Physiological and pharmacological activity, Xenobiotic and drug conjugation, Substrate specificities, Major groups SULT1 and SULT2, Tissue-specific expression and regulation
Archived at 2018/10/25